The Action of a Synthetic Pentasaccharide on Thrombin Generation in Whole Plasma - Béguin, S; Choay, J; Hemker, H C (Thrombosis and Haemostasis, 1989)
We investigated the effect on thrombin generation in plasma of the pentasaccharide that represent the AT II/binding site in heparin. This compound has no effect on the breakdown of thrombin in plasma. It dose-dependently inhibits the formation of thrombin in both the intrinsic and the extrinsic pathway. If coagulation is triggered by the complete prothrombinase complex (phospholipid – factor Va – factor Xa) under conditions in which the large majority of factor Xa is bound to the complex, the inhibition of prothrombinase activity is only minor. If no factor Va is present or if the prothrombinase activity is triggered by adding complete tenase (PL-FVIIIa-FIXa) or incomplete tenase (PLFIXa) to the plasma the inhibition by pentasaccharide is of the same magnitude as that in the intrinsic or extrinsic system.We conclude that the pentasaccharide inhibits blood coagulation by katalysing the inactivation of free factor Xa. In contrast to classical heparin it does inhibit the peak of thrombin formation in platelet rich plasma, probably because it is less subject to inactivation by heparin binding proteins from platelets than classical heparin is.
Keywords: Heparin; Pentasaccharide; Thrombin generation; Factor Xa